'Tracking of ideas': A method to evaluate the integration of ideas in cross-disciplinary collaboration. Issue 1 (9th November 2017) - Budd, Julia M
Abstract: Evaluating cross-disciplinary collaboration has generally been undertaken using disciplinary standards. However, this practice is increasingly being found to be inadequate due to the often contradictory nature of the methods used. It has been suggested that methods that consider the unique integrative nature of these studies be employed. This study describes the tracking of ideas method that was developed to consider the integration of ideas in group knowledge products developed by a cross-disciplinary group. The cross-disciplinary group was from the New Zealand disability field who used an eight-phase approach to brainstorm ideas over the course of a weekend on how to build an inclusive society for all New Zealanders. It was found that this new method was effective for tracking the ideas through numerous different artefacts and simplifying the complex path of those ideas. These artefacts included the worldviews, paradigms of disability and concept maps of the participants, the activity sheets from the group activities, the activity topics, and other artefacts made available to the groups. The findings from the tracking of ideas method were generally corroborated by the participant's reflections. Further research is needed to test the tracking of ideas method and to corroborate the findings with participants' perspectives.